The use of soil biostructures created by soil fauna ecosystem engineers fed with different organic materials as inoculum source of arbuscular mycorrhiza fungi on cocoa seedling - Laode Muhammad Harjoni Kilowasid; Muhammad Fahyu Sanjaya; Laode Sabaruddin; Rachmawati Hasid; Darwis Sulaeman; Andi Nurmas (Universitas Sebelas Maret, 2021)
Soil fauna as ecosystem engineers have the ability to create soil biostructures, with the capacity to save arbuscular mycorrhizal fungi (AMF) spores. This study therefore aims to investigate the AMF spore density in the biostructures created by cooperation between earthworms and ants with a different organic matter composition, and to analyze the biostructures’ potential as a source of AMF inoculum on cocoa seedlings. In the first experiment, a combination of earthworms and ants composition, as well as a mixture of G. sepium leaf (GLP), cocoa shell bean (CSB), and sago dregs (SD), was tested. Meanwhile, in the second experiment, the effect of biostructures on cocoa seedlings grown in unsterile soil,was examined. According to the results, the highest AMF spore density was obtained using 20 earthworms+10 ants with 50%GLP+50%CSB + 0%SD treatment. Furthermore, the total AMF spores were positively correlated with the total P value, but negatively correlated with the C/N ratio. Therefore, biostructure application increased AMF spores number in rhizosphere and the cocoa seedling’s root infection. Furthermore, biostructures resulting from the collaborative activity between different soil fauna ecosystem engineers were able to transmit AMF spores to infected plant roots growing in non-sterile soil.